Legal Protection of Indigenous People's Rights Through Strengthening the Licensing Principles Based on Social Sensitivity - Aditya, Zaka Firma; Al-Fatih, Sholahuddin (Universitas Negeri Semarang, 2021)
The issue of human rights in Indonesia towards the 21st century has shifted from violations committed by the government during the new order to the issue of human rights violations by multinational companies (corporate crime), because of natural resources exploitation is directly proportional to the increase in human rights violations. Many cases of human rights violations by business actors that occur in the form of annexation and seizure of indigenous peoples land that occurs every year. One of the causes of the many cases of human rights violations against indigenous peoples is due to the loosening of permits given by the government to companies wishing to exploit natural resources. Strengthening the Permits principle can be used as a strategic step in reducing the number of violations of poverty that occur to indigenous peoples. Permits used as a means of controlling human behavior which results in rights and obligations born of licenses.